Growth and physiological changes of Averrhoa carambola as influenced by water availability - Ismail, Mohd Razi; Awang, Muhamad (Universiti Putra Malaysia Press, 1992)
Utilizing an integrated soil moisture stress approach, two different experiments were conducted simultaneously to investigate the effects of water stress o.n growth and related physiological characteristics of Averrhoa carambola. The first experiment clearly indicated a high correlation between soil water availability and a reduction in plant vegetative growth. In the second experiment, there was a significant correlation between leaf water potential and a reduction in stomata conductance, transpiration rate and photosynthesis rate. The inhibition of photosynthesis mte was only apparent when leaf water potential was reduced to -0.85 MFa. However, chlorophyll content was only affected by a further reduction in water availability. The Telationship between physiological characteristics and vegetative growth is discussed.